Fire safety at the enterprises - Nidialko, A. (ТДАТУ, 2018)
EN: The purpose of the article is to investigate the causes of fires at the enterprises and their consequences. The article provides a graph of the number of people died during the fires as well as the main causes of the fires at enterprises and their preventive measures classification. UK: Метою статті є дослідження причин пожеж на підприємствах та їх наслідки. Наводиться графік кількості загиблих під час пожеж. Також представлені основні причини пожеж на підприємствах та класифікація їх запобіжних заходів.
Keywords: причин пожеж; запобіжні заходи; measures classification; causes of fires at the enterprises